Microstructural characterization of joints of maraging 300 steel welded by laser and subjected to plasma nitriding treatment - Lombardo, Sandro [UNESP]; Nascimento Ferreira, Renan [UNESP]; de Souza Santos, Lucas Augusto [UNESP]; de Jesus Silva, José Wilson; Bagio Scheid, Vladimir Henrique; Abdalla, Antonio Jorge (Trans Tech Publications, 2016)
Amongst the ultra high strength steels, the maraging steels have been noticed because they maintain the fracture toughness superior to other steels of their class. The main difference is the way they acquire resistance. While the conventional carbon steels raise their resistance by heat treatments forming harder phases such as martensite or bainitic constituents, the maraging steels harden by intermetallic particles precipitation. These steels are very promising for several applications, mainly for the aerospace or nuclear areas. In this work, tests of laser welding on a sample of maraging 300 steel, have been carried out, by applying aging at several times and temperatures and analyzing the influence of plasma treatment on the steel microstructure and resistance. The results are promising and show that this welding process is viable and can even be associated with nitriding to improve the surface characteristics. It was observed that the temperature choice and aging time are fundamental to reach high mechanical resistance levels. Temperature values about 480 ºC and time 10,800 seconds proved to be suitable for this treatment. The loss of strength in the welded joints, after the aging treatment, was less than 10%. It was also noticed that when the plasma nitriding treatment is applied, aging occurs simultaneously, therefore it is important to select temperature and treatment time in order to optimized the aging process as well.
Keywords: Aging; Laser welding; Maraging steel; Microstructural characterization; Plasma nitriding